Social responsibility and nationalism in school life: challenges of wasathiyah Islam - Ulya, Alya Khasanatul; Sa'adi (UIN Salatiga, 2025)
This research analyzes the implementation of wasathiyah Islam principles and the values of social responsibility and Nationalism through institutional policies and programs at MTs. NU Salatiga focuses on how these values are integrated effectively into religious, academic, and English education to foster a harmonious blend of Islamic values and national identity. The study was conducted at MTs. NU Salatiga, utilizing a descriptive qualitative method. The data was collected through observation, interview, audiovisual information, and documentation with ten respondents involving the principal, the vice principal for curriculum, the vice principal for student affairs, Islamic religious education and English subject teachers, and five students. Meanwhile, the data analysis involved three main steps: reduction, display, and conclusion. The result of the research proved that integrating the principles of wasathiyah Islam with social responsibility and nationalism values had been effectively implemented at MTs. NU Salatiga through well-structured policies and programs. This research provides theoretical implications by strengthening and expanding the concept of wasathiyah Islam as a practical educational approach to integrating religious values and Nationalism into the formal school curriculum.